Cascading Resilience: Leverage Points in Promoting Parent and Child Well‐Being. Issue 1 (March 2017) - Doty, Jennifer L.; Davis, Laurel; Arditti, Joyce A.
Abstract: While negative cascades have been well studied, little has been written on the promotion of upward spirals. We propose a conceptual model that situates parenting interventions as a leverage point in promoting positive cascades. We integrate broaden‐and‐build theory and social capital theory into the model to explain micro‐ and macro‐level patterns of change in longitudinal prevention studies, acknowledging that when socioeconomic resources are scarce, investment in parenting may be challenging. Parenting prevention programs provide evidence of improvements in effective parenting behaviors, promote increased confidence and a belief in parenting abilities, and over time may activate positive cascades that affect other domains in parents' lives, such as health and peer support. Resulting positive emotions are hypothesized to broaden coping and build long‐term resources that promote resilience. Social resources may then spill over to benefit individual, family, and community systems. Research methods for testing developmental cascades and practical applications are also considered.